Sustainable materials for artificial intelligence (AI) technology adoption for energy-efficient patient-centric healthcare solutions - Lakshmipriya Bachina; Anusha Kanagala; Sattibabu Korapu; P Ratnaraju (Journal of Education and Health Promotion)
Sustainable materials are also known as eco-friendly materials. A thorough examination of the relationship between sustainable materials, AI technology adoption, and patient-centered healthcare sustainable materials is crucial for reducing the carbon footprint of AI hardware and data storage in healthcare applications. Emphasizing eco-friendly practices aligns AI-driven healthcare with broader sustainability goals. The aim is to make it possible for energy-efficient AI technologies to revolutionize patient-centric healthcare while minimizing environmental impact and enhancing clinical outcomes. The development of sustainable and renewable resources to aid the adoption of artificial intelligence (AI)-driven healthcare solutions is the goal of sustainable materials for AI technology. The study takes a multidisciplinary approach, incorporating life cycle evaluation, a systematic review of literature, and Vos viewer keyword analysis. The study assesses the environmental impact of using sustainable materials in AI-driven healthcare solutions via life cycle assessment, addressing issues ranging from resource extraction to disposal. Artificial intelligence (AI) has quickly developed into a patient-centric approach. However, as the increasing adoption of AI-powered healthcare solutions has become more popular, there are growing worries about energy consumption, and the environmental impact of the materials used in AI devices. The use of sustainable materials in AI technology has the potential to improve patient-centric healthcare solutions by reducing energy consumption and limiting environmental impact. Adopting eco-friendly artificial intelligence hardware methods would concrete the way for a more sustainable and efficient healthcare ecosystem.